Efektivitas Perlindungan Perempuan dan Anak Korban Kekerasan di Provinsi Jawa Timur - Noftarida Dina Novita; Ertien Rining Nawangsari (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The increase in cases of violence against women and child requires resolution by the relevant agencies responsible for addressing this issue. One such agency is the East Java Provincial PPA Technical Implementation Unit (UPT PPA). The purpose of this study is to analyze the effectiveness of the UPT PPA of East Java Province in addressing cases of violence against women and child, using Duncan's organizational effectiveness theory, which has three components: goal achievement, integration, and adaptation. The research method used is a descriptive qualitative approach, employing observation, interviews, and documentation techniques. It was found that the organization has effectively implemented the goal achievement component. There is good integration among staff members, and the organization can adapt to changes. It is concluded that the organization is effective in carrying out its duties in handling women and children who are victims of violence, despite existing issues within the organization, which it has managed to overcome, thereby becoming effective.